Brain Gym Optimizing Concentration on Elementary Students - Wahyu Nur Pratiwi; Yuan Guruh Pratama (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research aims to find out the effect of Brain Gym on elementary student’s concentration. There was one group on this pra-experimental research, which measured the pre-test and post-test concentrations. 30 samples in this research were selected by purposive sampling technique from level 5 and 6 elementary students. These 30 students were set to do Brain Gym 3 times per week for 4 weeks. We find out from this research that group concentration’s pre test mean result was= 13.633 and for post-test was= 21.00. Wilcoxon signed rank test shows ρ=0,000. Those means that Brain Gym give significant effect on increasing students concentration. We can conclude that students can be increased concentration of learning by practicing Brain Gym regularly. Students may practicing this Brain Gym exercise at least 3 times per week at home in this pandemic condition, or before starting face to face learning when the pandemic is over